Influence of the developed agent "Sanskin" on the microflora of the skin of cow udder teats - Trukhanovych, T.; Perkiy, Yu. (Scientific Progress & Innovations, 2024)
1 % and lactic acid 2 % was developed. The work aimed at conducting a production study of the agent Sanskin, in particular, detecting the reduction of the microflora of the skin of udder teats while using the agent before milking. The study was conducted in the spring period on a dairy farm with livestock of more than 500 cows with a stable-free range cow breeding system. In the first group of animals: the right anterior and the right posterior teats of the udder were treated using agent Oxy Foam and the left anterior and the left posterior teats were treated using water (control). Pre-milking treatment of the studied teats using disinfectant included foam application, keeping it for 30 seconds, and further wiping dry using disposable paper towels. In the second group of animals, the right teats were treated by analogue with Sanskin with the help of a cup for disinfection by immersion for the whole teat length. Washes from the skin of udder teats were taken using sterile tampons before pre-milking treatment and repeatedly after the end of the milking process. The treatment using only water was found to reduce the number of microorganisms on the teat skin by 6.3 times (p≤0.01), while the use of disinfectant Oxy Foam – by 15.3 times (p≤0.001), and newly developed Sanskin by 13.4 times (p≤0.001). Washing with the use of warm water enables the reduction of 84 % of microorganisms from the teat skin to 14.3±2.1 CFU/ml of wash, while agents containing antibacterial substances enable reducing this number by 2–2.3 times more (р≤0.01). The use of disinfectant for pre-milking treatment – Oxy Foam contributed to the reduction in the number of bacteria of genus Staphylococcus by 5.1 times (p≤0.001), and of genus Streptococcus – by 4.3 times (p≤0.001) to 231±19 and 226±21 CFU/ml of the wash accordingly, which approximately corresponded to their number of bacteria 77 and 79 bacteria on 1 cm2 of the skin of cow udder teats. Treatment of skin of cow udder teats with the new agent Sanskin contributed to the reduction of staphylococci by 4.8 times (р≤0.001) and streptococcus by 4.5 times (р≤0.001) to 244±26 and 218±22 CFU/ml of the wash accordingly. After pre-milking treatment of the udder using both agents, the number of coliforms was reduced by hundreds of times to single cultures (3±0.5) per 1 ml of the wash of teat skin. Thus, while being used the developed agent Sanskin removes up to 79.3 % of microorganisms of the genus Staphylococcus, up to 77.6 % of bacteria of the genus Streptococcus and practically all coliforms from the skin of the cow udder teats and ensures perfect cleanness of udder teats before their milking. While used before milking, the agent Sanskin is not inferior in effectiveness compared to Oxy Foam.